2013
DOI: 10.5897/jtehs11.092
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acute ammonia toxicity in bluga (Huso huso), using natural zeolite

Abstract: The research was accomplished in order to study the efficiency of natural zeolite to prevent acute toxicity of ammonia on Huso huso. The study was performed using Water static method for 96 h. Fish with average weight 46 ± 5 g and total length 22 ± 4 cm were exposed to four different concentrations (15, 30, 50, 75 mg L -1 ) of ammonia salt. A group of fish was considered as control. Under stable condition, the lethal concentration of ionized ammonia was 50 mg L -1 during 96 h. In the lethal concentration of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…; Farhangi et al . ) and Persian sturgeon ( Acipenser persicus ) (Farhangi & Rostami‐Charati ). It was reported that in lethal concentration of ammonia, application of 15 and 12 g L −1 of the zeolite could prevent the mortality rate in beluga and Persian sturgeon, respectively.…”
Section: Improvement Of Aquaculture Water Quality Using Zeolitementioning
confidence: 99%
See 1 more Smart Citation
“…; Farhangi et al . ) and Persian sturgeon ( Acipenser persicus ) (Farhangi & Rostami‐Charati ). It was reported that in lethal concentration of ammonia, application of 15 and 12 g L −1 of the zeolite could prevent the mortality rate in beluga and Persian sturgeon, respectively.…”
Section: Improvement Of Aquaculture Water Quality Using Zeolitementioning
confidence: 99%
“…This new ion exchange/electrochemical regeneration process was successfully applied as a pilot scale test for continuous oxidation of ammonia from RAS water to N 2 (g) in one oxidation step. Natural clinoptilolite was used to prevent acute ammonia toxicity and increase survival rate in beluga (Huso huso) (Asgharimoghadam et al 2012;Farhangi et al 2013) and Persian sturgeon (Acipenser persicus) (Farhangi & Rostami-Charati 2012). It was reported that in lethal concentration of ammonia, application of 15 and 12 g L À1 of the zeolite could prevent the mortality rate in beluga and Persian sturgeon, respectively.…”
Section: Ammonia Removal By Different Types Of Zeolitesmentioning
confidence: 99%
“…Dices fluid was used to dilute blood to count RBCs and WBCs by haemocytometer chamber. Pipette was filled it to the marker (0.5) and diluted with the Dacie , s fluid was filled to mark (11) to make the dilution range 1:20, mixing well and remain for 5 min. The counting chamber was filled and left for about 5 minutes, then the WBCs were counted in the four corner primary squares of the chamber and the RBCs are counted in five secondary squares of the center primary square.…”
Section: Hematological Parametersmentioning
confidence: 99%
“…Hematological parameters are important for the evaluation of fish physiological status. Their changes depend on the fish species, age, cycle of sexual maturity and health condition (18) and they are closely related to the response of the animal to the environment , an indication that the environment where fish live could exert some influence on the hematological characteristic (11) . The present study aimed to calculate the period in which zeolite affects ammonia and determine the best treatment of zeolite cause reduce ammonia, as well as the effect of zeolite in different levels on hematological parameters including: RBCs, WBCs count, Hb content and PCV%.…”
Section: Introductionmentioning
confidence: 99%
“…7). Granulated CLP has been applied to help prevent acute toxicity of total ammonia (10–35 mg/L) to Huso huso (Farhangi et al , 2014), Acipenser persicus (Farhangi & Rostami-Charati, 2012), beluga (Asgharimoghadam et al , 2012), rainbow trout (Ghiasi & Jasour, 2012), angelfish ( Pterophyllum scalare ) (Ghiasi & Jasour, 2012) and Mazandaran common carp ( Cyprinus carpio ) (Ghiasi & Jasour, 2012). Most ammonia adsorption was recorded during the first 12 h of the experiment.…”
Section: Research Production and Applications Of Natural Iranian Zeomentioning
confidence: 99%